2021
DOI: 10.1016/j.jcrc.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of PEEP on mortality in ICU patients without acute respiratory distress syndrome: systematic review and meta-analysis with trial sequential analysis

Abstract: Objective To determine whether higher positive end- expiratory pressure (PEEP) could provide a survival advantage for patients without acute respiratory distress syndrome (ARDS) compared with lower PEEP. Methods Eligible studies were identified through searches of Embase, Cochrane Library, Web of Science, Medline, and Wanfang database from inception up to 1 June 2021. Trial sequential analysis (TSA) was used in this meta-analysis. Data synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 91 publications
(237 reference statements)
0
3
0
Order By: Relevance
“…Concomitantly, we observed a higher survival rate in patients that used PEEP ≤8 cmH 2 O. However, the outcome does not seem to be associated with the PEEP cut-off point in the literature (22,23). Gatinoni and co-workers (2015) concluded that there is not "a PEEP correct value" and that it must be titrated by taking into consideration several factors (e.g., oxygenation and hemodynamics) (19).…”
Section: Death Risk Associated With Peep and Paomentioning
confidence: 65%
See 1 more Smart Citation
“…Concomitantly, we observed a higher survival rate in patients that used PEEP ≤8 cmH 2 O. However, the outcome does not seem to be associated with the PEEP cut-off point in the literature (22,23). Gatinoni and co-workers (2015) concluded that there is not "a PEEP correct value" and that it must be titrated by taking into consideration several factors (e.g., oxygenation and hemodynamics) (19).…”
Section: Death Risk Associated With Peep and Paomentioning
confidence: 65%
“…However, when health professionals applied this value to normal lungs, there was no description of improvement in the outcome or time of hospital stay in the scientific literature yet ( 20 , 22 ). Therefore, according to individual ventilatory mechanics, we must make the best PEEP choice ( 23 ). At the same time, PaO 2 characterizes the degree of hypoxemia and hyperoxemia ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may in part be explained by the lower tidal volumes and lower respiratory minute volume in the intervention group, marking lung protective ventilation. Maintaining pH in a certain level is a common motivation to increase intensity of ventilation, and low bicarbonate has been identified as one factor leading to violation of lung-protective ventilation strategies [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the 6MWT distance, patients’ lung function presented significant improvement over 12 months in our study. Previous investigations showed that patients with ARDS presented mild abnormalities in lung spirometry following the ICU [ 32 , 33 , 34 ] or they may have presented fluctuations that were within the normal limits during 3 to 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%